2019
DOI: 10.1016/j.dib.2019.103963
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbial dataset of a foraging tribe from rural West Bengal - insights into unadulterated and transitional microbial abundance

Abstract: The human gut microbiome contributes to a broad range of biochemical and metabolic functions that directly or indirectly affect human system. Numerous factors such as age, geographical location, genetic makeup, and individual health status significantly influence the diversity, stability, and relative abundance of the gut microbiome. Of the mentioned factors, geographical location and dietary practices appears to explain a significant portion of microbiome variation. On the other hand tribal people living in g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Studies have shown that diet widely influences the gut microbiome and partially impacted human ability to extract and store calories as fat from food (Turnbaugh et al 2006;Menni et al 2017). In this context, a recent study of present authors on the gut microbial dataset of Savar tribal community of West Bengal showed that Savar gut microbial profile represents an abundance of unadulterated microbes constituted by Ruminococcaceae (15%), Succinovibrio (12%) and Bacteroides (31%) (Ganguli et al 2019). Another study conducted by Menni et al (2017) showed the possibility that Ruminococcus may be functionally linked to the lean phenotype, whereas, Gao et al (2018) in his study indicated a significant association between bacterial communities and underweight; therefore, the gut microbial composition may play a role in the regulation of human body composition as well as body weight.…”
Section: Discussionmentioning
confidence: 80%
“…Studies have shown that diet widely influences the gut microbiome and partially impacted human ability to extract and store calories as fat from food (Turnbaugh et al 2006;Menni et al 2017). In this context, a recent study of present authors on the gut microbial dataset of Savar tribal community of West Bengal showed that Savar gut microbial profile represents an abundance of unadulterated microbes constituted by Ruminococcaceae (15%), Succinovibrio (12%) and Bacteroides (31%) (Ganguli et al 2019). Another study conducted by Menni et al (2017) showed the possibility that Ruminococcus may be functionally linked to the lean phenotype, whereas, Gao et al (2018) in his study indicated a significant association between bacterial communities and underweight; therefore, the gut microbial composition may play a role in the regulation of human body composition as well as body weight.…”
Section: Discussionmentioning
confidence: 80%
“…The North-East Indian tribes, including Sikkim, were found to have similar food habits, though they belongs to different geo-political boundaries and shared ethnic affiliation. Sample sizes in the studies were different ranging from 193 [14] to merely 3 [16, 17].…”
Section: Analysis and Resultsmentioning
confidence: 99%
“…India has become a melting pot where the different lifestyle factors and food choices are being infiltrated in many indigenous and traditional lifestyles even in tribal communities [14] with the alteration of the gut microbiome profile [16, 18]. Although some communities still remained isolated so there are some chances to study gut bacterial diversity in these isolated tribal populations to compare the future changes in gut bacterial diversity due to food and life styles factors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations